2005
DOI: 10.1038/labinvest.3700255
|View full text |Cite
|
Sign up to set email alerts
|

An ex vivo model for functional studies of myofibroblasts

Abstract: Migration, proliferation and invasive growth of myofibroblasts are key cellular events during formation of granulation tissue in situations of wound healing, arteriosclerosis and tumor growth. To study the invasive phenotype of myofibroblasts, we established an assay where arterial tissue from chicken embryos was embedded in fibrin gels and stimulated with growth factors. Addition of serum, PDGF-BB and FGF-2, but not VEGF-A, resulted in an outgrowth of cellular sprouts with a pattern that was similar to the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…However, alpha-SMC actin-positive cells were only evident in the lumen of 2-week-old occlusions. These cells also were desmin negative, which led us to identify the cell type as a myofibroblast (16). At all later time points, the lumen cells were alpha-SMC actinnegative, except in the media of luminal microvessels.…”
Section: Methodsmentioning
confidence: 96%
“…However, alpha-SMC actin-positive cells were only evident in the lumen of 2-week-old occlusions. These cells also were desmin negative, which led us to identify the cell type as a myofibroblast (16). At all later time points, the lumen cells were alpha-SMC actinnegative, except in the media of luminal microvessels.…”
Section: Methodsmentioning
confidence: 96%
“…Furthermore, TGF-b1-induced proliferation of fibroblasts is mediated through the release of extracellular FGF-2 since FGF-2-blocking antibodies inhibited the proliferation of fibroblasts [19,61]. Finally, it has been shown that both PDGF and FGF-2 are important factors in the migration of myofibroblasts [64], suggesting that blockade of both pathways might be required to interfere with myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ER-b controls platelet-derived growth factor (PDGF), 28 a cytokine regulating the growth and the differentiation of fibroblasts into myofibroblasts. 29 Interestingly, PDGF is commonly expressed together with its receptors in the stroma of phyllodes tumor and rarely in fibroadenoma. 30 An ER-b-PDGF pathway could therefore be involved in the smooth muscle differentiation in these lesions.…”
Section: Er-b In Breast Fibroepithelial Lesionsmentioning
confidence: 99%